Perancangan Sistem Informasi Pengelolaan Webinar Berbasis Web - Purnama, Giri; Mulya, Imam (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Webinar activities that are carried out online allow a large number of participants from various origins, so manual management will be very troublesome for the organiser. The development of web-based applications allows developers to build applications quickly and easily. In the development stage of the web-based application, the first step that must be done is to create an application development design. The design of the application is based on the needs of the application manager which we can get from various ways such as studying related documents, interviews or literature studies on similar research. This research will conduct a needs analysis and apply it to the design of an application that will be used by webinar managers whose aim is to facilitate the process of managing webinar activities from the process of scheduling activities, registering participants to printing webinar certificates which can be done independently by the webinar participants.